Extraction of Rose Hybrid Tea Oil with Microwave Assisted Integration of Mahd as a Diffuser - Berkah, Fitroh Bawa; Devanda, Ilyas Rabbani; Wibisono, Enggar Sulistyo; Paramita, Vita (Vocational College of Universitas Diponegoro, 2024)
Rose flower have rich compound of oils that are used in many things for example in parfuem industries. Rose flower contains rich of oils fragrance such as eugenol, citronellol, geraniol, nerol, and linalool. This compounds has been used in variety of parfuem and many application has been used such as air freshener, softener, and diffusier. The objective of this research was to find out how to separate essential oils from rose flowers with Microwave Assisted Hydro Distilation and test them as diffusers and to find out the characteristics of essential oil. The extraction process takes place with two variables independent for time and power of extraction with their respective combinations of power: time (watt:minutes) namely; (300/15, 300/25, 300/35, 400/15, 400/25, 400/35, 500/15, 500/25, 500/35). The sample was prepared by make a solution with ratio of solvent (water distillation) and rose petals repeatedly 3:1 (v/m). During the research, an analysis of the yield of extract rose was carried out with a best result of 0.012% and the density produced 1,096 gr/ml. Organoleptic test was obtained with colored white limestone and typical odor of essential oil of rose flowers